Rhetorical ethics in handling of information - Francesca Vidal (Informatio, 2021)
In a world in which the strategic use of disinformation is becoming more and more the rule, it is necessary to ask how the credibility of information can be measured. The text gives indications as to why rhetorical skills are necessary for this and what the criteria for a credible style of speech are.